Soklin karbonatiittikompleksin Kauluksen alueen petrografia, geokemia sekä P-, Nb- ja REE-mineralisaatiot - Pynttäri, Juuso (Helsingfors universitet, 2015)
Sokli is located in the municipality of Savukoski in eastern Lapland, Finland, nearby the Russian border. GTK's research area of Kaulus is situated in the southern part of the Sokli carbonatite complex. The purpose of this work is to solve the petrography, geochemistry and P2O5-, Nb- and REE-mineralizations of rock types in the Kaulus region. In addition, the lithology of the area and the petrogenesis of these Devonian rocks are examined. A total of 1581.15 meters of drill core from 19 drill holes have been examined. Multi-element analysis has been done by XRF-method, trace elements have been analysed by ICP-MS-method and carbon has been analysed separately. From a total of 60 thin sections, 26 representative samples for the rock types of Kaulus have been selected, and were examined by EPMA, MLA and SEM. Some of the minerals have been imaged by BSE. The protolith rocks of Kaulus fenites are tonalite, granitic gneiss, gneiss, schist gneiss and amphibolite. The degree of metasomatism depends on the rock type and vicinity of carbonatite dikes. Felsic and intermediate fenites range from low-degree fenites through-medium degree fenites- to syenitic fenites. Phlogopitization reflect potassium metasomatism. No significant P2O5-, Nb- or REE-mineralizations were found in the fenites. Non-coherent mineralizations are local in respect to carbonatites. Metaphoscorites and metasilicocarbonatites are carbonated and alkali-metasomatized. The precursors of the metacarbonatites were probably magnetite olivinite, magnetite-olivine-amphibolite, olivine-pyroxenite, fenitized schist gneiss or gneiss and olivine-amphibolite. Metacarbonatites are enriched in P2O5 (2.6-4.0 %). Metaphoscorites occasionally have enriched Nb values (up to 1799 ppm), which may reflect to the composition of magmatic phoscorite. As CO2 concentrations increase in metacarbonatites, their REE-concentrations get similar with the REE-concentrations of carbonatites. According to average U/Th-ratios, Kaulus's carbonatites magmatic Stages have developed in the ...